The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10461-011-9992-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Prevalence of Injection Drug Use Among Adolescents and Young Adults in Large U.S. Metropolitan Areas

Abstract: Young injection drug users (IDUs) are at risk for acquiring blood-borne diseases like HIV and Hepatitis C. Little is known about the population prevalence of young IDUs. We (1) estimate annual population prevalence rates of young IDUs (aged 15–29) per 10,000 in 95 large U.S. metropolitan statistical areas (MSAs) from 1992 to 2002; (2) assess the validity of these estimates; and (3) explore whether injection drug use among youth in these MSAs began to rise after HAART was discovered. A linear mixed model (LMM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Finally, it is important to recognize that HIV prevention efforts may also be geared toward the subset of non-injecting drug users who are at risk for transition to injection [99]. Injection drug use among adolescents and young adults in the United States may be increasing [32, 100] and some have suggested that the recent trends in prescription opioid use may signal increasing transitions to injection drug use [101, 102]. Risk behaviors and the injection and sex risk networks of this new generation of IDUs will affect the future course of the HIV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to recognize that HIV prevention efforts may also be geared toward the subset of non-injecting drug users who are at risk for transition to injection [99]. Injection drug use among adolescents and young adults in the United States may be increasing [32, 100] and some have suggested that the recent trends in prescription opioid use may signal increasing transitions to injection drug use [101, 102]. Risk behaviors and the injection and sex risk networks of this new generation of IDUs will affect the future course of the HIV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent trends show that although both HIV (Broz et al, 2014; Centers for Disease Control and Prevention, 2009) and HCV (Amon et al, 2008) prevalence have steadily declined among older PWID, high-incidence of HCV infection (Page et al, 2009; Zibbell et al, 2015) and HCV outbreaks among younger PWID (Centers for Disease Control and Prevention, 2011; Leuchner et al, 2008) are occurring. In addition, IDU has been steadily increasing among youths (Chatterjee et al, 2011; Tempalski et al, 2013), and high levels of risky injection and sex behaviors continue to be reported in this group (Broz et al, 2014; Hahn et al, 2010; Rondinelli et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…9 The increase in HCV infections among youth and young adults may be attributable to prescription opioid misuse and injection drug use, which has also been increasing in similar age groups. [10][11][12][13] It has been demonstrated that some prescription opioid abusers transition to injection drug use, 6,[14][15][16][17] putting them at increased risk for acquiring blood-borne infections such as HCV and HIV.…”
Section: Introductionmentioning
confidence: 99%